The Power of the Underutilized and Neglected Medicinal Plants and Herbs of the Middle East - Shahrajabian, Mohamad H.; Sun, Wenli (Reviews on Recent Clinical Trials, 2024)
The Middle east and North Africa harbour many native species with pharmaceutical and nutraceutical potential. Since the beginning of history, food and herbal medicinal plants have been an essential part of human lives and the traditional Middle Eastern healthcare system. The notable medicinal plants that have been mentioned in the Bible, which are common in West Asia and some regions of North Africa, are Aloe vera, anise, balm, cassia, cinnamon, cumin, flax, and fig. Chemical components of Aloe vera are aloin, sinapinic acid, catechin, chromone, myricetin, quercitrin and syringic acid. Anethole, safrole, and estragole are the main chemical components of anise. The chemical components of cassia are coumarin, emodin, cinnamyl alcohol, and cinnamaldehyde. The major chemical ingredients of cumin are terpinene, cuminaldehyde, sabinene, thujene, and thymoquinone. The goal of this article is to review the considerable health benefits and pharmaceutical benefits of medicinal herbs and plants that have been neglected and underutilized in the Middle East and North Africa, as well as to promote their utilization. On the basis of the results, the experimented neglected medicinal plant can offer various advantages when used together with conventional medicinal treatments for various health conditions, such as palliative care in managing the side effects of conventional treatments, access to a wider range of treatments, increased patient satisfaction, and improved emotional and mental well-being. Moreover, consuming medicinal plants may help to manage and prevent diabetes, cancer, and heart disease with notable anti-tumor, and anti-inflammatory properties.
Keywords: traditional medicine